Walisongo and the Notion of Abrasive Strategies in Countering Radicalism in Indonesia - Abu Hapsin (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2022)
This paper focuses on the role of Walisongo in addressing religious radicalism in Indonesia. Religious radicalism has emerged due to excessive internet consumption in today’s technologically advanced world. Consequently, it necessitates serious efforts to tackle this issue, including exploring local knowledge to counteract religious radicalism behaviors. This qualitative study adopts a library research approach, incorporating diverse sources to explore theories and knowledge related to these phenomena. This study found the importance of implementing strategies that promote wise behavior and nonviolent approaches in reducing religious radicalism. These efforts primarily involve initiating a change in people’s mindset toward Islam. The success of the strategy to reduce the level of radicalism can be carried out through regional management (geographical considerations), arts management or cultural engagement, health management (medical aspects), fostering noble behavior (akhlāq al-karīmah), marriage alliances, and deepening religious knowledge.